Being God's image : why creation still matters - Imes, Carmen Joy, 1977-; Middleton, J. Richard, 1955- (2023)
"What does it mean to be human? For this timeless question, the Bible offers truths for the flourishing of all creation. Carmen Imes recovers the theologically rich creation narratives and explores the implication of our kinship relationship with God, considering what it means for our work, gender relations, creation care, and eternal destiny"--
Includes bibliographical references and index.
Keywords: Bible. -- Criticism, interpretation, etc; Image of God; Identification (Religion); Identity (Psychology) -- Religious aspects -- Christianity; Identity -- Religious aspects -- Christianity